(untitled) (Global Journal of Human-Social Science, 2019)
This study aims to identify the municipalities of Minas Gerais with water crisis and to analyze the main measures for the environmental management of water resources In different parts of the world access to this natural good already shows serious concerns whether for the availability or the way it is distributed There is poorly planned use of them The research was developed under the framework of journalistic articles reports interviews about the cities that declared an emergency situation listing which measures are being carried out by municipalities in a situation of water crisis The actions promulgated by the mayors are immediate and punctual as a rotation of supply without building a long-term water resources management plan there is a lack of municipal planning or a project to avoid decreeing public calamity or emergency due to lack of water In this way it is understood that territorial governance may be threatened since the lack of long-term public policies compromises the territorial governance of municipalities especially their natural resources